The Effectiveness of the Family Hope Program (PKH) in Improving the Economic Welfare of Poor Communities in Lemahabang Village, Indramayu District, Indramayu Regency - Sonia Meilianti; Luthfi Faisal Natsir; Ibrahim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to determine the effectiveness of the Family Hope Program (PKH) in improving the economic welfare of poor communities in Lemahabang Village, Indramayu Regency. The focus of the study was directed at the extent to which the implementation of PKH is understood by the community, the accuracy of recipient targets, the timeliness of aid distribution, the achievement of objectives, and the tangible changes felt by beneficiaries. The research method used was qualitative with a descriptive approach, where data were obtained through in-depth interviews, observation, and documentation which were then analyzed by reducing data, presenting data, and drawing conclusions. The results showed that PKH was quite effective in helping the poor, especially through conditional assistance that supports the education and health needs of families. However, several obstacles were also found, such as inaccurate recipient data, delays in information, and limited nominal aid that did not fully meet household needs. The conclusion of this study is that PKH has made a positive contribution to the economic welfare of the community, although improvements are still needed in data collection, distribution mechanisms, and increasing the amount of aid so that the program's objectives can be optimally achieved.